'When people pray, a god is born... This god is you!’: an introduction to religion and god in digital games - Wiemker, Markus; Wysocki, Jan (Online - Heidelberg journal of religions on the internet, 2014)
Notions of religion in media are not only found in literature, movies, or music but also in the growing field of digital games. We want to dive into this field by thinking about in what ways religion can be and is used by developers in the narration of a game and what religious motifs we encounter in our research. This essay attempts also to show that cultural studies can make a significant contribution to a better understanding of digital games, by regarding the ‘game-text’ together with its production contexts and acquisition processes. We try to highlight this trough an examination of different aspects of religion in games and with a special focus on how the notion of ‘god’ is used in games. We will discuss the genre ‘god games’ that puts the player in a position to influence different layers of a complex game system, like a tribe, a city, or other social or economic systems, etc. There we will ask what this genre has to do with concepts of ‘god’ or gods. Ultimately we will explore games that present more distinct images of gods and show how concepts from different religious contexts, like Greek or Japanese mythology, are used in a game’s narrative.